2017
DOI: 10.1111/php.12806
|View full text |Cite
|
Sign up to set email alerts
|

Various LED Wavelengths Affected Myofiber Development and Satellite Cell Proliferation of Chick Embryos via the IGF‐1 Signaling Pathway

Abstract: An effect of monochromatic light illumination on muscle mass has been discovered in chickens; however, its effect on the development of embryonic muscle remains unclear. Our previous studies demonstrated that monochromatic green light promoted satellite cell proliferation and muscle growth in posthatching broilers. In this study, we investigated the effects and mechanisms of monochromatic light exposure on muscle development in late embryogenesis. Seven hundred and fifty fertile broiler eggs were randomly assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Furthermore, our study demonstrated that monochromatic green light promoted satellite cell proliferation and increased the number of satellite cells in control saline treatment. These findings are consistent with our previous results, that is stimulation with monochromatic green light during incubation enhanced the skeletal muscle growth and satellite cell proliferation in late-embryogenesis (E15-E20) [10] and early stage (P1-P21) [8] of chicks. In this study, we further investigated the effects of monochromatic green light stimulation on the expression of Pax7 and Myogenic regulatory factors ( MRFs ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, our study demonstrated that monochromatic green light promoted satellite cell proliferation and increased the number of satellite cells in control saline treatment. These findings are consistent with our previous results, that is stimulation with monochromatic green light during incubation enhanced the skeletal muscle growth and satellite cell proliferation in late-embryogenesis (E15-E20) [10] and early stage (P1-P21) [8] of chicks. In this study, we further investigated the effects of monochromatic green light stimulation on the expression of Pax7 and Myogenic regulatory factors ( MRFs ).…”
Section: Discussionsupporting
confidence: 93%
“…Light penetrate the skull and have direct effects on avian pineal gland or hypothalamus [2, 3], which regulate the endocrine activities to affect the physiological functions, including muscle growth [4], morphogenesis of interlimb stepping [5], satellite cell mitotic activity [6] and quality properties of meat [7]. Meanwhile, monochromatic green light influences the satellite cell proliferation activity, number, myofiber areas and muscle mass from the embryonic period in chick [810]. However, how monochromatic light affect the satellite cell proliferation is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that increased activity of TRP channels induces ROS generation (66) and thus the activation of the Ras pathway, a key pathway involved in the modulation of the activity of small GTPases, ultimately leading to the modulation of calcium signalling and apoptosis (67). Hence, these mechanisms may explain current findings which indicate that blue light induces significant increases in ROS production (19,(68)(69)(70)(71)(72). However, evidence also suggests this may be due to the effects of blue light on mitochondrial activity, inducing increases in ROS production as a result of the stimulation of the electron transport chain (73).…”
Section: Opsinsmentioning
confidence: 78%
“…A second Scopus database search was undertaken to evaluate the effects of green light PBM using the terms described in Figure 3b. An initial search resulted in 236 articles being identified and these articles were subsequently screened for suitability, which then identified 32 relevant articles for further review (18,32,33,64,68,69,79,164,168,171,176,177,186,197,205,209,(212)(213)(214)(215)(216)(217)(218)(219)(220)(221)(222)(223)(224)(225)(226)(227).…”
Section: Kazemi Khoo Et Al 2013(184)mentioning
confidence: 99%